Propuesta de sostenibilidad y mejora en procesos técnico-administrativos para un food truck en la ciudad de Bogotá (2021)
A process of continuous improvement is essential for success, results are improved and improving them means reaching the maximum benefits. The methodology developed throughout the scientific article will provide the necessary tools to translate the improvement in the technical-Administrative processes for the Órale SAS food company, designing possible corrective actions, taking as added value a possible sustainability strategy and responsible consumption through of renewable energies that promote the positioning of the company and customer loyalty.